Hypermedia Content Transmission Plan - Managing the Broadcast/Multicast Delivery - Josué, Marina Ivanov Pereiraé; Moreno, Marcelo Ferreira; Costa, Romualdo Monteiro de Resende (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
Nowadays hypermedia content may be delivered over different platforms, such as Terrestrial DTV, IPTV and the Web. Therefore hypermedia presentation engines must be designed taking into consideration the specificities of their supported networks to provide the expected QoE levels. Presentation engines employ some content analysis to help on the task of maintaining QoE. However, when the content includes pushed data, this analysis should be transferred to the server side for building the so-called Transmission Plan. The Transmission Plan is a data structure that predicts the time when media objects should be transmitted and for how long, in order to optimize end-to-end resource usage. This work proposes a framework for managing the push-mode delivery of hypermedia content. The framework is generic enough to be instantiated over different content delivery scenarios. Introductory instantiation scenarios and initial results are also discussed.